Quantifying faecal glucocorticoid metabolites in rock hyraxes Procavia capensis (Pallas, 1766) living in an urban green space - Ganswindt, Andre (University of Pretoria, 2021)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2020.